On the statistical analysis of the harmonic signal autocorrelation function - Sienkowski, Sergiusz; Krajewski, Mariusz (Zielona Góra: Uniwersytet Zielonogórski)
The article presents new tools for investigating the statistical properties of the harmonic signal autocorrelation function (ACF). These tools enable identification of the ACF estimator errors in measurements in which the triggering of the measurements is non-synchronized. This is important because in many measurement situations the initial phase of the measured signal is random. The developed tools enable testing the ACF estimator of a harmonic signal in the presence of Gaussian noise.
Keywords: harmonic signal; autocorrelation function; bias; variance; mean squared error